Design review of the electrical system for air traffic control tower facility at Hamad International Airport, Doha, Qatar - Reyes, Rudilyn S. (Manila Professional Regulation Commission, 2015)
The Air traffic Control Tower Facility substation is supplied from 11KV NDIA site distribution system composed of two 2000/2666 KVA, oil filled, ONAF transformers, 11KV/415/240V (nominal voltage), delta-star, with secondary windings solidly grounded. The transformers were sized with future load in consideration and equipped with forced air capability when required during full load conditions. The substation is of double-ended configuration variety with tiebreaker normally open. When one transformer is inoperative, the other is capable of supplying the entire line up that feeds the main building but excludes the chilled water facility which is disconnected from the system during one-transformer-in-service situation but is appointed with its own back up power during this occurrence. The power distribution system was built with solid redundancy in effect. Transformer 1 supplies the East Wing of the Complex where the Control Tower and associated Air Navigation (ANS) offices are located, including one set of units for the chilled water facility. Transformer 2 supplies the West Wing where the Approach Radar Facility, the Main Equipment Room and other ANS offices are situated, including the other set of units for chilled water facility. These sets of units alternate in operation. When one is on duty, the other is on standby. In the event that the feed of electricity from the grid fails and both transformers are declared unserviceable, an automatic switch-over to standby generators will be initiated. Two 1600 KVA diesel-driven back up generators are available, dedicated for each transformer and a third, an 800 KVA diesel driven generator is provided for chilled water facility. In addition, a parallel online double conversion UPS subsystem is installed that offers totally conditioned clean power full time to sensitive ATC servers and computer system. These protects equipment from common utility problems such as power surges, voltage spikes, frequency variation, etc., through continuous conversion from AC to DC to AC providing steady, tightly regulated power output. Since the duty inverter is continuously online at all times and at all conditions, no transfer time or interruption of power to the load will be experienced during commercial power disruptions. During such disruption, the UPS can deliver up to 30 minutes of available power supply to designated essential circuits. All cables and circuit breakers ratings were derived and compared to the existing installed fixtures through thorough and painstaking calculations. Ampacity considerations, voltage drop evaluation, derating factors application, short circuit and protection and insulation coordination calculation are incorporated in accordance with the prescribed local and international standards.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-653G donated by Mr. Jaime V. Mendoza.
Keywords: Buildings -- Electric equipment